Social representation of masculine and feminine sports among Saudi adolescents - Munirah Alsamih (Frontiers in Psychology, 2024)
IntroductionThis study examined how certain sports are represented as masculine or feminine in Saudi adolescents, namely, which sports adolescents associate with males and which sports they associate with females. Previous research aligned with this concern was conducted within Western culture; however, there is a need to shed light on how the issues of social representation of masculine and feminine sports affect other cultures such as Middle Eastern cultures.MethodsA survey was completed by 280 Saudi adolescents, aged between 12 and 17 (M = 13.5, SD = 1.3). The survey contained open-ended recall questions that asked participants to name three masculine, feminine, and natural sports.ResultsMost participants were familiar with using feminine and masculine terminology to describe sports, and nearly half had personally used gendered terms to describe sports. Overall, the participants generated 2,195 names of various sports, with the majority classified as natural (appropriate for both men and women), many masculine, and the fewest feminine.DiscussionThe connection between specific sports and masculinity or femininity can restrict the activities of adolescents who do not conform to traditional gender roles. Also, adolescents who are interested in sports that are not typically associated with their gender may experience social stigma or exclusion, which can discourage their participation. Therefore, it is important to establish inclusive environments in sports, regardless of the gender.